PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF DENGAN MENGGUNAKAN SOFTWARE ADOBE FLASH CS6 PROFESSIONAL PADA SISWA SMP KELAS VIII - Febrita melati setiawan; Asni johari; muswita muswita (BIODIK, 2015)
The humans’ respiratory system is one of the material subject biology in eight grades of junior high school. Human respiratory system material requires an understanding of the concept. The use of interactive multimedia is one way to presenting the material. Based on the observation in SMP 24 Jambi found that the students are difficult to understand the material because the teacher is not optimal in using the media. Therefore, the teachers need a learning media to describe the material. Interactive multimedia flash can be used as the media. The purpose of this research is to develop and to know the students responses in the multimedia interactive learning material on the human respiratory system for junior high school in VIII class using Adobe Flash Professional Cs6. This research is the development research. The research design in this study follows the ADDIE development model.ADDIE development model has five stages: analysis, design, development, implementation and evaluation. Before the multimedia product tested it will be validate by the expert to determine the feasibility of the product, the team experts are material expert and media expert. The result of the validation from material expert obtained 87.1 % score with very good categories and the result of the validation from media expert obtained 80% score with good categories. The students’ response to the media for small group is in very good category with of 87.8% and for large group is classified in very well category with 87.1%. Based on the result, the conclusion this study is the multimedia interactive learning on the material of the human respiratory system got a very good response from the students. Multimedia interactive learning on the material in the human respiratory system can help the teacher in the learning process and can be used as self-learning that students can use at school and outside school hours.